Programa de atención e intervención psicosocial orientado a la construcción de habilidades psicosociales para la vida desde la gestión del riesgo frente al estrés laboral en golden flash (2021)
Studying the dynamics and natural organizations of work today has begun to be of great importance. Over time, advances to improve the quality of life of human beings have increased productivity and actions at the corporate level to provide services or some type of product to society, which means improving the work environment for health of the workers and the benefit of the companies themselves (Velasco, 2012).